The Relationship of leadership activities on the morale and job satisfaction of the service crew of McDonald's fastfood chain (Lipa City Branch) - Dimaandal, Mark Ivann C. (Manila: National University, 2006)
The study aimed to describe the relationship of leadership activities on the morale and job satisfaction of the service crew of McDonald's fast food chain (Lipa City Branch).
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of Tables -- Chapter 1. The Problem and its Background -- Chapter 2. Review of Related Literature and Studies -- Chapter 3. Research Methodology and Design -- Chapter 4. Presentation, Analysis, and Interpretation -- Chapter 5. Summary of Findings, Conclusions, and Recommendations -- Appendix -- Bibliography.
Research Method : Random Survey
Includes bibliography